Suitability evaluation for lowland rice in inland valleys in West Africa. In Japanese - Fujii, H.; Gumma, Murali K.; Thenkabail, Prasad S.; Namara, Regassa E. (2010)
A GIS based model developed by the authors are applied for selecting suitable rice cultivation area in inland valleys that has high potential for rice production in West Africa where rice consumption is increasing very rapidly. The model has the following features. 1. The model is to evaluate the suitability of the land for lowland rice based on score distribution maps respectively made by the data of 29 evaluation parameters. 2. The parameters are classified into 4 categories; bio-physical, technical, socio-economic and health-environmental parameters. 3. Each scored map(layer)is integrated to obtain total scores by multiplying a weight which is determined by the importance of parameters. The suitability for rice in two study sites was evaluated using the model. Mankran and Jolo-Kwaha watershed selected as the study sites from different agro-ecological zone in Ghana. Applying the data of 12 parameters acquired in the study sites to the model, "very suitable? or "suitable? occupies around 30% in Mankran study site and around 60% in Jolo-Kwaha study site.